Cutaneous manifestations of underlying malignancies presenting to a tertiary care teaching hospital - Kilaru, Krishna Rajesh; Kaja, Keerthana; Garimella, Venkateswara Rao (International Journal of Research in Dermatology, 2019)
Background: The skin is the largest organ in the human body. Many types of cancers can cause lesions to appear on the skin. An association between systemic malignancy and cutaneous manifestations has long been recognized. Recognition of these lesions is important for diagnosis at early stages and hence we analyzed the presentation of various skin manifestations in relation to various malignancies. Methods: We did a prospective study from June 2016 to November 2017 on 50 confirmed cases of internal malignancy with skin manifestations attending the DVL and Oncology OPD of NRI Medical College and General Hospital and Cancer Institute. Detailed history, cutaneous examination, and investigations were done. Results: Study population included 23 males and 27 females. The majority of cases (34%) were aged above 60 years. In females, reproductive tract malignancies were the highest (37%). In males, Non-Hodgkin’s lymphoma (17.3%) and carcinoma rectum (17.3%) were commonly seen. Generalized pruritus was the major presenting cutaneous manifestation (16.4%). Paraneoplastic dermatoses were the most frequent cutaneous markers (67.2%). Conclusions: Cutaneous manifestation from an internal malignancy is a relatively uncommon phenomenon. But at times, they may be the only presenting feature. Cutaneous paraneoplastic syndromes are important clinical markers that may precede or occur simultaneously or after the diagnosis of a given neoplasm and recognizing them may lead to a higher chance of cure and better prognosis for the patient.